Factors affecting social impacts of provincial level science and technology tasks after its completion in Nghe An province in the period of 2005-2015 - Vo Hai Quang; Nguyen Dinh Binh; Nguyen Huu Xuyen (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
Assessing the social impact of science and technology tasks after its completion is a matter of interest to researchers and managers in recent years. With the goal of quantifying the factors affecting the social impact based on the feedback of the beneficiaries of the results of the provincial science and technology tasks appraised in the period 2005-2015 (case study of Nghe An province) and their social impacts in the period 2006-2020. The article provides evidence and evaluates factors affecting social impact, thereby suggesting solutions to improve the positive social impact of science and technology tasks after its completion of Nghe An province in the period of 2021-2025. The study collected 381 valid survey questionnaires in Nghe An province from enterprises, cooperatives and individual business households, who applied the results after its completion from provincial science and technology tasks in Nghe An Province in the period of 2005-2015. Code: 21081401